STRATEGI BISNIS GAJAH MADA SWALAYAN DALAM MENGEMBANGKAN USAHA - Fransika Citra Ayu (Jurnal Niaga & Bisnis (e-journal), 2015)
ABSTRACT Economic growth in the era of globalization is marked by the development of the business in all areas. One of today's growing businesses are Small and Medium Enterprises (SMEs). Small and medium enterprises are often found today are small and medium enterprises engaged in the retail business, the supermarket. This study aims to determine the business strategy undertaken by Gajah Mada Supermarket in Lubukpakam, Deli Serdang. The strategy includes pricing strategies and marketing strategies. The method used in this study is a qualitative method, ie the research methods used to examine the natural objects, where the researcher is the key instrument. Data collection techniques triangulation (combined), data analysis is inductive, and qualitative research results further emphasize the significance of the generalization. The technique will be used to blunt the data source is the data collection techniques in depth interviews, participant observation, and the study of literature. The result showed that the strength of Gajah Mada Supermarket is a good service, product packaging is neat and clean, affordable price, and location of Gajah Mada Supermarket is located, provides a variety of products, supply of goods is always on time. Weakness owned by Gajah Mada Supermarket is insufficient parking space, lack of promotion as well as employees stopped working and recruit new employees. While the opportunities that are owned by Gajah Mada Supermarket is the advancement of technology, public tastes changing, and people's purchasing power. Threats owned by Gajah Mada Supermarket is the emergence of similar competitors and unstable prices of goods, the promotion of self-service competitors, and competitors' promotional prices.   Keywords : Gajah Mada Swalayan, Strengths, Weaknesses, Threats, and Opportunity